Similar within their differences. A comparative study of Bogotá Futuro and the Proyecto Orgánico para la urbanización del Municipio de Buenos Aires - Arango López, Diego (Universidad del Rosario, 2016)
This article seeks to analyze two urbanism projects developed simultaneously during the 1920’s in Bogota and Buenos Aires. Bogotá Futuro and the Proyecto Orgánico para la urbanización del Municipio de Buenos Aires are two projects with major differences in their technical characteristics, their formal features, and the theoretical bases upon which they rely. However, as they were established, in both cases they generated a similar transformation on the means of understanding the city, as well as its current and future problems. This study uses a comparative method intended to understand the development of thought and action processes in relation to the instruments that support them. Therefore, the analysis will allow us to comprehend how the use of different tools in separate and different urban societies with divergent social and political characteristics may generate convergent changes in its mechanisms of urban transformation. Finally, this article pretends to contribute to a transnational study of Latin American urban history.